INTERACTION DESIGN DEVELOPMENT OF REAL TIME OBJECT DETECTION MOBILE APPLICATION FOR LOW VISION WITH USER-CENTERED DESIGN APPROACH - Arifazzahra, Mutiara
The Indonesian Central Bureau of Statistics (2020) survey proves that 5% of the total Indonesian population has a disability. One form of disability is visual impairment called low vision. The right to equal opportunity and accessibility for persons with disabilities as Indonesian citizens is regulated in Act No. 8 of 2016 (UU No. 8 Tahun 2016). One of the implementations of these rights is to develop assistive technology. This study focuses on the development of the interaction design for assistive technology in the form of a real time object detection mobile application aimed at answering one of the problems experienced by low vision, identifying items around. The design is developed with a user-centered design approach that focuses on user needs. The final result of the design is a high-fidelity prototype consisting of application flow and interface design. The feasibility of the design was evaluated by conducting usability testing with people with low vision. The usability and user experience goals of the developed design are effective to use, efficient to use, and helpful. The achievement of these goals was assessed by scoring the Task Completion Rate, System Usability Scale (SUS), Single Easy Question (SEQ), comparison of the number of steps with a similar application, Intrinsic Motivation Inventory (IMI) value/usefulness subscale, and additional questions to respondents. After two iterations of design implementation and evaluation, the final design achieved a Task Completion Rate score of 100% (out of 100%), SUS score of 86.5 (out of 100), SEQ score of 6.56 (out of 7), fewer steps compared to a similar application, and IMI score of 6.69 (out of 7). Based on these figures, it can be concluded that the overall usability and user experience goals have been achieved.